Characteristics of precipitation in the Athens area, Greece - Paliatsos, A. G.; Nastos, P. T.; Tzavelas, G.; Panagiotakos, D. B. (Fresenius Environmental Bulletin, 2005)
In this work, the characteristics of the long-term precipitation time series in Athens area (1891-2000). Statistical analysis shows that higher values of annual precipitation observed in the 1930s, while the lowest values were observed in the 1890s and 1980s. There is no significant trend in the annual precipitation time series. Moreover, the annual number of days with high precipitation (ANDHP) remains constant, during the investigated period. Spectral analysis by the Blackman-Tukey method that applied to the time series of ANDHP, showed in most cases peaks at frequencies corresponding to the following time periods: about 2.6 and 4.0 years. Β© by PSP.
Keywords: Athens; Athens [Attica]; Attica; Eastern Hemisphere; Eurasia; Europe; Greece; Precipitation; precipitation (chemistry); Precipitation statistics; Southern Europe; statistical analysis; Trends; World